The Effect of Using Fix-Up Strategy Toward Students Reading Comprehension at The Tenth Grade of SMAN 1 Kecamatan Harau - Nuri Ainah; Melyann Melani; Reflinda Reflinda; Veni Roza (Jurnal Pendidikan dan Sastra Inggris, 2025)
The goal of this study was to find out how the Fix-up method affected the reading comprehension of class X students in SMAN 1 Harau District. Students' difficulties with reading comprehension while learning English are the impetus for this study. Reading scores for students are low. The majority of students did not achieve the KKM or Minimum Standard Score, as indicated by their daily reading tests. Vocabulary is lacking among students. Many students are still unable to comprehend the sentence's meaning when presented with advertisement text using common vocabulary, and they lack motivation to read. The researchers compared two classes using quantitative methods and a quasi-experimental research design in this study. This study's participants were students in class X at SMAN 1 Harau District, with X-E.7 serving as the control group with 30 students and X-E6 as the experimental group with 27 students. A reading test serves as the research instrument. On SPSS 26, an independent sample T-test was used to analyze the data. Students who were taught using the Fix-up strategy and students who were taught without using the Fix-up strategy achieved significantly different levels of reading comprehension. strategy. The fact that the p-value is lower than the alpha value (0.000 0.05) demonstrates this. It is possible to draw the conclusion based on these data that students' reading comprehension is significantly affected by the use of the fix-up strategy.